Author Correction: Organophosphorus diisopropylfluorophosphate (DFP) intoxication in zebrafish larvae causes behavioral defects, neuronal hyperexcitation and neuronal death - Alexandre Brenet (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.